The duration of untreated psychosis among U.S. Latinxs and social and clinical correlates - Santos, Maria M.; Kratzer, Maya; Zavala, Jaqueline; Lopez, Daisy; Ullman, Jodie; Kopelowicz, Alex; Lopez, Steven Regeser (Frontiers in Psychiatry, 2023)
Purpose: This study (a) documents the duration of untreated psychosis (DUP) and (b) examines both social and clinical correlates of DUP in a sample of U.S. Latinxs with first-episode psychosis (FEP). Methods: Data were collected for a longitudinal study evaluating a community education campaign to help primarily Spanish-speaking Latinxs recognize psychotic symptoms and reduce the DUP, or the delay to first prescribed antipsychotic medication after the onset of psychotic symptoms. Social and clinical variables were assessed at first treatment presentation. A sequential hierarchical regression was conducted using √DUP to identify independent predictors of the DUP. A structural equation model was used to explore the association between DUP predictors, DUP, and clinical and social correlates. Results: In a sample of 122 Latinxs with FEP, the median DUP was 39 weeks (M=137.78, SD=220.31; IQR = 160.39-5.57). For the full sample, being an immigrant and having self-reported relatively poor English-speaking proficiency and self-reported strong Spanish-speaking proficiency were related to a longer delay to first prescribed medication after psychosis onset. For the immigrant subgroup, being older at the time of migration was related to a longer delay. Self-reported English-speaking proficiency emerged as an independent predictor of the DUP. Although the DUP was not related to symptomatology, it was associated with poorer social functioning. Low self-reported English-speaking ability is associated with poorer social functioning via the DUP. Conclusion: Latinxs with limited English language skills are especially at high-risk for experiencing prolonged delays to care and poor social functioning. Intervention efforts to reduce the delay in Latinx communities should pay particular attention to this subgroup.